Hydatid cyst of papillary muscle concomitant with brain involvement. Issue 2 (13th January 2023) - Taherkhani, Maryam; Yeganegi, Houra; Bagheri, Amin
Abstract: Background: Cardiac hydatidosis is a rare disease and the subepicardial region of the left ventricular is commonly affected. However, papillary muscle concomitant with brain involvement has not been previously reported. Case: We report a 44 years old man who complained of headache along with no cardiac symptoms. The patient was diagnosed with cerebral hydatid cyst. Through preoperative cardiac consultant, transthoracic echocardiography revealed cardiac hydatid cyst confined to the anterolateral papillary muscle. Medical treatment was started promptly and successful surgical excision of all cysts was performed. The patient had an uneventful recovery and follow up at 3 months. Conclusion: Early diagnosis of cardiac HC by echocardiography is recommended in all patients with hydatid disease, regardless of HC location.